155 Research to support the implementation of a public health policy on helmet use in alpine ski areas. (1st September 2016) - Goulet, Claude; Hagel, Brent E; Hamel, Denis; Tremblay, Benoit
Abstract : Background: From 1995 to 2000, the rate of injury in Québec, Canada, ski areas significantly increased. This problem coincided with an increase in the number of snow-parks. Before suggesting injury prevention measures, some questions had to be answered: Are helmets effective? Does helmet use result in a false-sense of security? Can head-neck-helmet biomechanics increase spinal injury risk? Do expert skiers and snowboarders need a helmet? Is there an increased risk of serious injury in snow-parks? The aim of this paper is to outline how a series of epidemiologic studies significantly contributed to support the implementation of important safety measures in alpine ski areas. Methods: A series of case-control studies were undertaken. They were based on the information gathered through ski patrol injury report forms (IRF). Depending on the specific study, between 4, 377 and 97, 408 IRFs were analysed. Results: The results of these studies suggest that: helmets are effective in reducing the risk of any head injury (adjusted odds ratio [AOR] = 0.71; 95% CI: 0.55–0.92); helmet use is not associated with a false-sense of security leading to riskier behaviours; helmets do not increase the risk of neck injuries; expert alpine skiers are at greater risk of head-neck injuries compared with beginners (AOR = 1.86, 95% CI: 1.65–2.10); for skiers (AOR = 1.36; 95% CI: 1.21–1.53) and snowboarders (AOR = 1.14, 95% CI: 1.05–1.23), injuries sustained in snow-parks compared with other slopes are more likely to require ambulance evacuation. Conclusions: Considering this evidence, the Québec Government modified a provincial regulation to make compulsory the use of helmets in all snow-parks. The Québec Ski Areas Association and the Québec Government also implemented a practical guide for building and operating snow-parks. Results show a reduction in the rates of head-neck injury from 1997–1998 season (5.07/10, 000 visits; 95% CI: 4.84–5.31) to 2012–2013 season (3.27/10, 000 visits; 95% CI: 3.13–3.41).